Efficacy of DVIU and intralesional injection of mitomycin C in the treatment of bulbar urethral stricture - Hosseini, Jalil; Allameh, Farzad; Najafi, Saman; Salimi, Hojat; Sadeghzadeh, Zahra; Hosseini, Mohammad Ali (Archives of Men's Health, 2020)
Background and aim: To find if intra-operative local injection of Mitomycin-C after internal Urethrotomy in patients with urethral stricture can improve the outcome of surgery. Materials and Methods: Seventy patients were allocated in two groups randomly and data were analyzed. The case group (n=35) was treated by internal Urethrotomy with intra-operative local injection of Mitomycin-C. The control group (n=35) was underwent standard internal Urethrotomy. The patients were followed after removing catheter and for 6 months after surgery by USS PROM questionnaire and uroflowmetry. Results: A significant difference was observed in terms of urodynamic indices like Q-max (p-value=0.006) and urine flow pattern (p-value=0.025) after internal Urethrotomy in the local injection of Mitomycin-C group and control group, six months after surgery. In the case group, in the six months after operation, only 2.9% of patients had Q-max less than 15 and no one had obstructive pattern, while in the control group, 25.7% of patients had Q- max less than 15 and 17.1% had obstructive pattern. However, the patient's satisfaction history did not show any significant difference in post-internal Urethrotomy voiding status in the local injection of Mitomycin-C group and control group, either immediately after removal of the urethral catheter (p-value=1) and six months after surgery (p-value=0.198). Also, no significant difference was observed in terms of urodynamic indices like Q-max (p-value=0.771) and urine flow pattern (p-value=1) after internal Urethrotomy in the local injection of Mitomycin-C group and control group, immediately after removal of the urethral catheter. Conclusions: Intra-operative local injection of Mitomycin-C after internal Urethrotomy can be regarded as a safe and efficient technique which has several advantages including lower cost. Lower recurrence rate of urethral stricture is the main effect of local Mitomycin-C application that is more prominent after six months follow up.